Postmodern Strategic Management and Its Impact on Achieving Organizational Excellence in Tourism Organizations: An Exploratory Study of the Opinions of a Sample of Individuals Working in Tourism and Travel Companies in Baghdad Governorate: Manajemen Strategis Pasca-Modern dan Dampaknya terhadap Pencapaian Keunggulan Organisasi di Lembaga Pariwisata: Studi Eksploratif terhadap Pendapat Sebagian Individu yang Bekerja di Perusahaan Pariwisata dan Perjalanan di Provinsi Baghdad - Breesam, Dr. Khaleel Ibrahim (Indonesian Journal of Public Policy Review, 2026)
General Background: Strategic management has evolved to incorporate postmodern perspectives that emphasize flexibility, innovation, and dynamic organizational capabilities. Specific Background: Organizations increasingly rely on postmodern strategic approaches to achieve higher levels of organizational excellence in complex and competitive environments. Knowledge Gap: Despite this development, limited empirical research examines how postmodern strategic management contributes to organizational excellence within specific institutional contexts. Aims: This study aims to analyze the relationship between postmodern strategic management and organizational excellence. Results: The findings indicate a significant positive relationship between strategic management dimensions and organizational excellence, supported by statistical analysis using Partial Least Squares Structural Equation Modeling. Novelty: The study offers an integrated empirical perspective on postmodern strategic management within an applied organizational setting. Implications: The results provide insights for decision-makers to adopt adaptive strategic practices that support continuous improvement and organizational excellence. Keywords: Postmodern Strategic Management, Organizational Excellence, Strategic Practices, PLS-SEM, Management Studies Key Findings Highlights Strategic adaptability contributes to higher institutional performance outcomes Decision-making flexibility supports improved administrative practices Integrated management approaches strengthen long-term organizational development